ANALISIS RISIKO KEHILANGAN PASCA PANEN PADA RANTAI PASOK KENTANG DENGAN METODE HOUSE OF RISK - Amilia, Winda; Rusdianto, Andrew Setiawan; Hita, Muhammad Arga; Hapsari, Dea Nawang (Jurnal Penelitian Sains dan Teknologi Indonesia, 2025)
Potatoes, as an agricultural vegetable crop, are highly susceptible to damage during post-harvest and distribution processes. Post-harvest activities involve multiple actors, including farmers, agents, market traders, and street vendors. The involvement of numerous actors in the supply chain can lead to damage that affects potato quality. This study aims to analyze the risks of quality loss during post-harvest processes and design handling strategies to reduce supply chain risks for potatoes. The research employs the House of Risk (HOR) method, which consists of two phases. The findings reveal that the types of quality degradation affecting potatoes are primarily due to mechanical damage, classified into abrasion, cracking, puncture, cutting, bruising, splitting, tearing, and skin cracking. These risks were identified as being caused by 10 risk agents. Among them, four key risk agents were selected and analyzed to determine appropriate mitigation strategies. The recommendations for risk management and mitigation actions are expected to minimize the risks of mechanical damage in the potato supply chain in Magetan Regency.